Sosialisasi Rekam Medis dan Pencegahan Duplikasi Rekam Medis Pada Petugas Admisi Rumah Sakit Umum Anwar Medika - Laila, Nisful; Huda, Nurul; Arwani, Arwani (Jurnal Abdimas Jatibara, 2023)
Improving the quality of human resources is closely related to education because education is the main effort that will be able to make human resources of high quality. Education will be successful if the condition of human resources is maintained in good health, therefore health is also an important factor to support efforts to improve the quality of human resources. Admissions must increase their knowledge and skills about medical records so that they can carry out their duties professionally and understand their role optimally. minimize duplication of medical record numbers.  The method used is health socialization and promotion by informants who have been selected according to the admissions office as the respondent.  the results obtained are the priority problems that occur in the numbering of medical record files. The problem that occurs in the numbering of medical record files is human error in employees who sometimes forget or are not careful in checking patient data in hospital applications (EHOS) which makes patient data not appear in application databases and computers which sometimes long and difficult to access when inputting medical record numbers and also patients who sometimes forget to bring their identity cards, causing missed communication to admissions officers, with fishbone diagrams and 5 whys, the root cause of the problem has been found, namely the lack of accuracy of admissions staff in inputting data, computers that are old and difficult to access as well as patients who forget to bring their identity cards which make the service long. 43 Solving the problem that must be done is to provide guidance or procedures to the admissions officer on how to check the hospital application (EHOS), strengthen human resources to be more thorough, and check repeatedly when registering a patient then if duplication has already occurred then the admissions officer must coordinate with the medical record officer to deactivate one of the medical record numbers that have not been registered for a long time and replace it with a newer one